Magnetohydrodynamics Inclination Effects on Couette Fluctuating Micro-Gas Flow - Moyi, Aliyu Usman; Sani, Ashafa (UUM Press, 2025)
An analytical investigation is conducted in the laminar flow regime to examine the impacts of Magnetohydrodynamics (MHD) inclination on Couette fluctuating basic micro-gas-flow, in which the bottom plate remains fixed while the top plate swings in its plane with sinusoidal velocity. Using a transformation technique, the partial differential equations that govern the flow situation have been reduced to a system of analytically solvable ordinary differential equations. The impact of MHD inclination on the dimensionless velocity and skin friction's numerical values are displayed in a detailed analytical and graphical form. The analysis's conclusion reveals that velocity rises with increasing phase angle values but drops with increasing inclination angle, magnetism, and frequency of the fluctuating driving force